Hadhanah Reconceptualization in Institutional Child Care Practices - Robi’ Alighan Hanantaqi; Wildani Hefni; Moh. Lutfi Nurcahyo (Academia Open, 2026)
General Background Hadhanah in Islamic family law traditionally regulates child care based on biological parental responsibility, particularly after divorce, with an emphasis on welfare and protection. Specific Background Contemporary social conditions show increasing reliance on child social welfare institutions, such as the Putri ‘Aisyiyah Sumbersari Jember institution, which implement structured, value-based child care integrating religious, social, and developmental dimensions. Knowledge Gap Classical fiqh and the Compilation of Islamic Law primarily frame hadhanah as an individual parental right, leaving limited conceptual clarity regarding institutional caregiving practices. Aims This study aims to reconceptualize hadhanah within institutional child care practices by integrating Islamic law, Kuhn’s paradigm shift theory, and modern social welfare perspectives. Results The findings indicate a shift from individual to collective guardianship, where institutions function as subjects of hadhanah oriented toward the best interests of the child, encompassing holistic protection including physical, psychological, social, and spiritual needs. Institutional practices demonstrate alignment with maqāṣid syariah and child protection principles, emphasizing structured, professional, and child-centered care. Novelty This study introduces hadhanah as a form of collective institutional responsibility (hadhanah jama’iyah), redefining caregiving beyond lineage-based relations into social-professional frameworks. Implications The reconceptualization bridges classical Islamic jurisprudence, national legal frameworks, and contemporary child welfare practices, providing a more adaptive and contextually relevant model for Islamic family law and institutional child care systems. Highlights: Institutional caregiving replaces lineage-based custody with collective responsibility frameworks. Holistic protection integrates spiritual, psychological, educational, and social dimensions of care. Child-centered orientation prioritizes long-term development and rights fulfillment. Keywords: Reconceptualization, Hadhanah, Child Social Welfare Institutions